Mast cells promote scar remodeling and functional recovery after spinal cord injury via mouse mast cell protease 6. Issue 5 (25th February 2016) - Vangansewinkel, Tim; Geurts, Nathalie; Quanten, Kirsten; Nelissen, Sofie; Lemmens, Stefanie; Geboes, Lies; Dooley, Dearbhaile; Vidal, Pia M.; Pejler, Gunnar; Hendrix, Sven
Abstract : An important barrier for axon regeneration and recovery after traumatic spinal cord injury (SCI) is attributed to the scar that is formed at the lesion site. Here, we investigated the effect of mouse mast cell protease (mMCP) 6, a mast cell (MC)‐specific tryptase, on scarring and functional recovery after a spinal cord hemisection injury. Functional recovery was significantly impaired in both MC‐deficient and mMCP6‐knockout (mMCP62/2) mice after SCI compared with wild‐type control mice. This decrease in locomotor performance was associated with an increased lesion size and excessive scarring at the injury site. Axon growth‐inhibitory chondroitin sulfate proteoglycans and the extracellular matrix components fibronectin, laminin, and collagen IV were significantly up‐regulated in MC‐deficient and mMCP6 –/– mice, with an increase in scar volume between 23 and 32%. A degradation assay revealed that mMCP6 directly cleaves fibronectin and collagen IV in vitro. In addition, gene expression levels of the scar components fibronectin, aggrecan, and collagen IV were increased up to 6.8‐fold in mMCP6 –/– mice in the subacute phase after injury. These data indicate that endogenous mMCP6 has scar‐suppressing properties after SCI via indirect cleavage of axon growth‐inhibitory scar components and alteration of the gene expression profile of these factors.—Vangansewinkel, T., Geurts, N., Quanten, K., Nelissen, S., Lemmens, S., Geboes, L., Dooley, D., Vidal, P. M., Pejler, G., Hendrix, S. Mast cells promote scar remodeling and functional recovery after spinal cord injury via mouse mast cell protease 6. FASEB J. 30, 2040–2057 (2016). www.fasebj.org